MCSA/MCSE Implementing, Managing, and Maintaining a Microsoft Windows Server 2003 Network Infrastructure (Exam 70-291) : Study Guide and DVD Training System. - Shinder, Dr Thomas W. (Microsoft .Net Study Guide & DVD Training Systems., 2003)
Provides coverage of Microsoft Exam 70-291 and features one-of-a-kind integration of text, DVD-quality instructor-led training, and Web-based exam simulation and remediation. This study guide and DVD training system gives students coverage of official Microsoft exam objectives and test preparation.